ChemInform Abstract: Tunable Cascade Reaction of Aryl Diazonium Salts and Trialkylamine: Synthesis of Monofluorinated Arylhydrazones and gem‐Difluorinated Azo Compounds. Issue 29 (29th June 2016) - Guo, Rui; Zhang, Zhengjuan; Shi, Feng; Tang, Pingping
Abstract: Using H2 O, monofluorinated arylhydrazones are obtained.